Factors influencing the willingness to perform bystander cardiopulmonary resuscitation on the workplace: a study from North-Eastern Italy - Riccò, Matteo; Berrone, Mirco; Vezzosi, Luigi; Gualerzi, Giovanni; Canal, Chiara; De Paolis, Giuseppe; Schallenberg, Gert (Acta Biomedica Atenei Parmensis, 2020)
Background. Early bystander cardiopulmonary resuscitation (CPR) improves the chances of successful resuscitation and survival. However, few data are available regarding the willingness to perform CPR among First Aid Attendants on the Workplace (FAAWs) in Italy. The present study was performed in order to identify current attitudes of Italian FAAWs towards CPR.Methods. Between February and June 2017, FAAWs from the Autonomous Province of Trento were asked about their willingness to perform CPR through a structured questionnaire assessing their knowledge about CPR, and the reasons for hesitancy. A cumulative knowledge score (KS) was eventually calculated.Results. A total of 123 FAAWs (male 57.7%, mean age 45.2 years ± 10.1) completed the questionnaire. About 1/3 of participants (32.5%) had previously performed First Aid procedures. Overall, 77.2% exhibited willingness to perform CPR, and such attitude was more frequently reported by subjects younger than 40 years (29.5% vs. 10.7% in older subjects; p = 0.045), perceiving First Aid training as useful (98.9% vs. 84.7%, p = 0.002), and exhibiting a better knowledge of CPR (KS ≥ 75%: 47.4% vs. 15.3%). The reasons for the unwillingness were inadequate knowledge and doubt regarding whether they could perform the techniques effectively. Eventually, KS was identified as the main predictor for willingness to perform CPR (OR 4.450, 95%CI 1.442 – 14.350).Conclusions. Willingness to perform CPR was seemingly high, and knowledge of CPR techniques was its main predictor. These findings emphasize the importance for an accurate CPR training, as well as for the surveillance of the quality of qualification courses.